Head rush Ajax - McLaughlin, Brett (O'Reilly, 2006)
Sick of creating web sites that reload every time a user moves the mouse? Tired of servers that wait around to respond to users' requests for movie tickets? It sounds like you need a little (or maybe a lot of) Ajax in your life. Asynchronous programming lets you turn your own web sites into smooth, slick, responsive applications that make your users feel like they're back on the information superhighway, not stuck on a dial-up backroad. But who wants to take on next-generation web programming with the last generation's instruction book? You need a learning experience that's as compelling and.